Determination of Design Solution for a 6x6 ATV with an Electromechanical Transmission - Evseev Kirill (EDP Sciences, 2021)
The article provides an overview and analysis of the current state of development of 6x6 ATVs and the scope of the developed ATV, as well as technical characteristics of 6x6 ATVs with a mechanical transmission. The choice and justification of design solutions for a 6x6 ATV with an electromechanical transmission are presented. Also, the selected structural and design solutions for the developed ATV are substantiated based on the selected electric drive scheme taking into account the traction calculation for the selected electric motor.